A Stretchable‐Hybrid Low‐Power Monolithic ECG Patch with Microfluidic Liquid‐Metal Interconnects and Stretchable Carbon‐Black Nanocomposite Electrodes for Wearable Heart Monitoring. (16th October 2018) - Li, Yida; Luo, Yuxuan; Nayak, Suryakanta; Liu, Zhuangjian; Chichvarina, Olga; Zamburg, Evgeny; Zhang, Xiaoyang; Liu, Yang; Heng, Chun Huat; Thean, Aaron Voon‐Yew
Abstract: A stretchable electrocardiogram (ECG) patch (SEP) that monolithically integrates ECG monitoring chip‐on‐board (COB) with polydimethylsiloxane (PDMS) and liquid‐metal interconnects is presented. The 4.8 × 4.8 cm 2 SEP is conformal and robust to mechanical deformation. The use of a silicon‐on‐insulator rigid complementary‐metal‐oxide‐semiconductor chip allows sophisticated power management and signal processing. The chip's dense inputs/output pads are interfaced with coarser liquid‐metal interconnects using a dual‐sided COB design. A robust ECG signal response (≈100 mVp–p up to 1 kHz), subjected to mechanical deformation and moisture is demonstrated. The SEP allows up to 10% stretch, providing sufficient pliability to enable conformal contact to the human chest. Low profile soft carbon black‐PDMS nanocomposite electrodes, robust to deformation, enable good skin contact and allow for low‐noise signal acquisition that is comparable to larger commercial wet electrodes. Abstract : A hybrid rigid stretchable electrocardiogram (ECG) patch that provides quality real time ECG monitoring is demonstrated. The custom designed ECG chip, through the integration of rigid chip‐on‐board with small footprint with Galinstan interconnects, allows high performance circuitry while ensuring the patch is highly compliant. Furthermore, integrated soft carbon black‐polydimethylsiloxane nanocomposite as sensor electrodes with comparable performance to commercial wet electrodes is presented.